Are large prospective trials on antidepressants in mental disorders seeding trials? A descriptive study of trials registered on ClinicalTrials.gov - Ioana-Alina Cristea; Astrid Chevance; Florian Naudet; Daniele Fanelli; Samuel Martineau (BMJ Open)
Objectives This descriptive study of registered trials aimed to identify large clinical trials on antidepressants for mental disorders: (1) to assess what proportion could be labelled as ‘seeding trials’ (trials for marketing purposes) and (2) to describe their methodological characteristics and outcomes.Design A search was conducted across all trials registered on ClinicalTrials.gov by drug name in March 2017.Setting All trials registered in the database of ClinicalTrials.gov were screened. Large registered studies were received and studies focusing prospectively on the effects of antidepressants in mental health disorders. Specific data items were extracted automatically, and subsequently inspected, corrected and completed by hand.Participants Prospective studies were selected focusing on the effects of antidepressants in any mental health disorder with 800 participants or more planned for inclusion.Main outcome measures Three members from the study team independently assessed the following ‘seeding trial’ characteristics in each registered study: a high level of involvement of the product manufacturer in the study design, in the data analysis and reporting of the study, an abnormally low ratio of patient numbers to study site, spin and/or omissions of clinically relevant findings in the abstracts, and conclusions that focused on secondary endpoints and surrogate markers. Secondary outcomes were the exploration of a functional outcome and suicidality.Results 31 trials were identified from clinical trials database. 18/31 were published (58%). 8 of these 18 (44%) studies were identified as possible seeding trials. 13/31 (42%) large trials planned to explore functioning and 5/31 (16%) suicidality.Conclusions Large trials are rare in the field of antidepressant research. Some could be ‘seeding trials’. Few explored suicidality. Identifying seeding trials from incomplete data entries in registries, especially when almost half of the studies were still unpublished, posed considerable challenges. The delay between our research and publication limits the strength of our conclusions.PROSPERO registration number CRD42017065591.